Pengaruh Current Ratio, Debt Ratio, And Return On Asset Terhadap Financial Distress - Ameilia Damayanti; Rianto Rianto (Fakultas Ekonomi dan Bisnis Universitas Pancasila Jakarta, 2023)
This study aims to analyze the effect of current ratio, debt ratio, and return on asset on financial distress in m food and beverage sub-sectors listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The dependent variable in this study is financial distress and the independent variables in this study are current ratio, debt ratio, and return on asset. Determination of the sample is done by purposive sampling using several criteria. The number of samples selected as many as 13 companies from a total population of 30 companies. In this study, the data analysis used was SPSS. The results of this study indicate that debt ratio, and return on asset have no effect on financial distress, while current ratio have effect on financial distress.